Network Security Analysis Using Virtual Private Network in Vocational School - Sari, Yosi Nofita; Irfan, Dedy; Huda, Asrul (Jurnal Paedagogy, 2022)
Every organization chooses a virtual private network (VPN) as their top option since it is a practical and secure solution. Through the use of a virtual private network, this study seeks to evaluate the network in SMK (VPN). The descriptive qualitative research used in this study was carried out at the lab of SMK Negeri 1 Ampek Angkek. Data were gathered through observation, interviews, and document analysis studies. The method of data analysis employed descriptive analysis. The results of this study indicate that the activity on the VPN network is better than the Non-VPN because the activities carried out in the VPN tunnel are not known by others. Users find it simpler to finish their daily agenda as a result.